O papel do turismo na atividade econômica: uma abordagem a partir do PIB, da arrecadação de ICMS e dos gastos públicos - Penedo, Vitor Orletti (2024)
Tourism is an activity that drives the economy across various spectrums. Brazil has potential for this activity that can boost its growth and revenue. Therefore, this dissertation seeks to investigate the impacts of tourism on Gross Domestic Product (GDP) and Value Added Tax (ICMS) revenue at both national and regional levels in Brazil, using a panel data approach for the period from 2004 to 2021. Explanatory variables included spending on culture, sports and leisure, tourism expenditure, and tourist arrivals. Models were estimated considering both fixed and random effects. Results reveal that, on a national scale, the main drivers of GDP and ICMS were tourist arrivals and spending on culture. For the Northeast region, both spending on culture, sports and leisure, and tourist arrivals showed significance in both fixed and random effects models.